Evaluation of pain during intravitreal aflibercept injections. Issue 1 (January 2018) - Doguizi, Sibel; Sekeroglu, Mehmet A.; Inanc, Merve; Anayol, Mustafa A.; Yilmazbas, Pelin
Purpose: To evaluate the pain associated with intravitreal aflibercept injections. Methods: The study included 119 patients who received intravitreal aflibercept injection at a single institution. Pain was evaluated by visual analog scale (VAS) immediately after the injection of 2 mg/0.05 mL aflibercept into the vitreous cavity using a 27-G needle. Additional variables including age, sex, indication for the injection, injection site by quadrant (superotemporal or inferotemporal), position during injection (sitting or supine), number of previous intravitreal injections in the study eye, presence of diabetes mellitus or hypertension, and lens status (phakic or pseudophakic) were recorded and assessed with self-reported pain scores. Results: Pain scores on the VAS ranged from 9 to 70, with a median of 18. Indications for injection included diabetic macular edema (21.0%), macular edema secondary to central retinal vein occlusion (12.6%), and neovascular age-related macular degeneration (66.38%). Pain did not significantly correlate with any of the recorded variables. Conclusions: This is the first series evaluating the pain associated with intravitreal aflibercept injections. We demonstrated that pain associated with intravitreal aflibercept injection is generally mild with low pain scores.